Anticipating Learning Loss in Students: A Study of Government Policy and Teacher Innovation - Robbi Rahim; Muqarranah Sulaiman Kurdi; Rispa Ngindana; Musyarrafah Sulaiman Kurdi; Wim Johannes Winowatan (AL-ISHLAH: Jurnal Pendidikan, 2023)
The phenomenon of learning loss is no stranger to the world of education, the presence of Covid-19 has exacerbated this condition. If it is not anticipated, it will have an impact on decreasing the quality of the nation's generation. This research aims to analyze the policies of the Indonesian government and teachers in tackling learning loss in students. The research method used is Systematic Literature Review (SLR) with metasynthetic data analysis techniques. This study found that the Indonesian government's policies are 1) online learning; 2) implementation of three curricula; 3) teacher training and mentoring; and 4) provision of textbooks and digital teaching tools. Meanwhile, innovations made by teachers include 1) psychosocial assistance; 2) utilization of technology; 3) approach; 4) design varied learning; 5) numerical literacy assistance; 6) blended learning; 7) home visit; and 8) development of learning media. Thus, to minimize learning loss, government policies and teacher innovation are needed.